The preparation of national school pupils for technical training and industrial life - Ryan, Frederick W. (Statistical and Social Inquiry Society of Ireland, 1917)
The recent action of the Commissioners of National Education in Ireland instituting an official certificate for pupils leaving the higher standards in Day National Schools makes of practical interest the consideration of other provisions, long overdue, in the Primary Schools of the country. Some notes are made in this paper?from unavoidable circumstances rather loosely put together?on the need of the provision of Manual Instruction in Woodwork; of Medical Treatment for pupils of Day National Schools; and the organisation of Continuation Classes for such pupils on leaving the Day Schools for the working world.
Read February 23rd, 1917
Keywords: National education; Evening classes; Technical training and education; 314.15